Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.12659/msm.891204
|View full text |Cite
|
Sign up to set email alerts
|

Serum γ-Glutamyltransferase Level is Associated with Periodontal Disease Independent of Drinking Habits in Japanese Adults

Abstract: BackgroundNon-alcoholic fatty liver disease is considered a hepatic manifestation of metabolic syndrome. Periodontal disease is a mild chronic inflammatory disease with systemic effects, and many studies have indicated an association between metabolic syndrome and periodontitis. In the present study, we investigated the relationship between periodontitis and liver biochemical parameters according to alcohol drinking habits through a cross-sectional study based on data from Japanese people in occupational setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…However, elevated serum γ-glutamyltransferase (GGT) level is associated with periodontal disease (> 4 mm periodontal pockets) in adults without drinking habit [152]. GGT is a deviation enzyme mainly present in liver, kidney and pancreatic cells.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld) and Periapicalmentioning
confidence: 99%
“…However, elevated serum γ-glutamyltransferase (GGT) level is associated with periodontal disease (> 4 mm periodontal pockets) in adults without drinking habit [152]. GGT is a deviation enzyme mainly present in liver, kidney and pancreatic cells.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld) and Periapicalmentioning
confidence: 99%
“…Several parameters such as probing depth, clinical attachment level, or percentage of bleeding on probing, have been used in other studies to assess the possible relevance of periodontal diseases to systemic diseases. Morita et al reported the association between periodontal pocket depth ≥4mm and serum GGT levels ( 16 ). Among the parameters, ABL and clinical attachment level represent the result of tissue destruction by periodontitis, which existed in the past ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption, smoking habits, age, blood pressure, and body mass index (BMI) were considered as covariates, according to previous studies reporting the risk factors for elevated serum liver enzyme levels ( 16 , 21 - 23 ). Alcohol drinking and smoking habits were surveyed using a self-administered questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between periodontitis and nonalcoholic fatty liver disease, which is considered a hepatic manifestation of metabolic syndrome, has been well-documented 10,11,29) . Furusho et al 10) had reported that infection with Porphyromonas gingivalis, an important periodontal pathogen, exacerbated high-fat diet-induced steatohepatitis in mice.…”
Section: Discussionmentioning
confidence: 99%